PENGEMBANGAN MEDIA CANVA BERBASIS YOUTUBE PADA MATERI MENJAGA DIRI DARI PERGAULAN BEBAS DAN ZINA: DILIHAT DARI ASPEK VALIDITAS DAN PRAKTIKALITAS - Junpriadi, Andika; Hazmar, Al Afif; Vebrianto, Rian (Perspektif Pendidikan dan Keguruan, 2026)
The purpose of this study is to develop a YouTube-based Canva application learning media on the material of protecting oneself from promiscuity and adultery, and to analyze its feasibility from the aspects of validity and practicality in Senior High Schools (SMK). This study uses the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects involved three (3) experts (certified lecturers/teachers) for media validation, twenty (5) Islamic Religious Education teachers, and thirty (30) SMK students for practicality testing. Data were collected directly in the field using a Google Form-based validity and practicality questionnaire instrument, which was then analyzed quantitatively using the SPSS program. The results of the study showed that the Canva and YouTube Media products were categorized as Valid Without Revision (VTR) by the expert team (X = 2.76) and Very Practical by teachers (94.4%) and students (95.0%). So this research provides implications that the YouTube-based Canva application media is a very suitable alternative for educators to produce innovative and relevant learning media to the characteristics of vocational school students